Estilos e estratégias de aprendizagem do inglês: um estudo de caso no ensino fundamental - MONASSA, Sulenir Palmeira (Universidade Federal do Pará, 2011)
This study aims at investigating the learning styles and strategies of a group of Elementary School students of a Belém public school. We also identified students goals and objectives in learning English. The principles of qualitative research were adopted to collect and analyze the data of this case study. The instruments used were questionnaires, self- verbal report protocols and field notes. Browns (1994) Felder and Solomans (1993) and Oxfords (2003) proposals provide rationale in order to classify learning styles. We also chose Oxfords theories (1990) to describe and classify learning strategies (2003). In order to make the foreign language learning (FLL) in public schools more effective, we describe two models of strategies based instruction which can be integrated into regular courses: Strategies-Based Instruction (SBI) by Cohen (1998) and Strategy Training Model by Oxford (1990). Results of this study describe the styles and strategies of a class of 8th graders of a Public School. We state that once these characteristics are identified, teacher and students can create learning situations which are more effective.